2023
DOI: 10.1021/accountsmr.3c00106
|View full text |Cite
|
Sign up to set email alerts
|

Porous Liquids Open New Horizons: Synthesis, Applications, and Prospects

Dechao Wang,
Yunpan Ying,
Yangyang Xin
et al.

Abstract: Conspectus Though the idea of liquids with accessible porosity seems counterintuitive, porous liquids (PLs) have indeed demonstrated themselves to hold great promise in versatile fields, thus arousing great attention and interests from both academic and industrial communities since the concept of PLs was first proposed in 2007. PLs are a novel class of a flowing liquid system that possesses accessible permanent porosity, and they integrate the processable advantages of liquids with superior accommodative capac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(6 citation statements)
references
References 59 publications
0
6
0
Order By: Relevance
“…Despite their high potential, applications of PLs are nearly always restricted to gas sorption and gas separation, even when the host particles are large. ,, While metal extraction using solid porous silica or other similar materials is well developed, , it is surprising that very little research has been conducted to date with LPs . PLs were recently considered for metal adsorption.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite their high potential, applications of PLs are nearly always restricted to gas sorption and gas separation, even when the host particles are large. ,, While metal extraction using solid porous silica or other similar materials is well developed, , it is surprising that very little research has been conducted to date with LPs . PLs were recently considered for metal adsorption.…”
Section: Introductionmentioning
confidence: 99%
“…2,8,9 While metal extraction using solid porous silica or other similar materials is well developed, 10,11 it is surprising that very little research has been conducted to date with LPs. 12 PLs were recently considered for metal adsorption. Hemming et al have shown the possibility of encapsulating nanoparticles of gold, platinum, and palladium during the synthesis of a functionalized silicabased PL with the aim of developing a liquid support for heterogeneous catalysis.…”
Section: ■ Introductionmentioning
confidence: 99%
“…As an emerging type of liquid material, porous liquids (PLs) have attracted much attention in the past decade due to their great ability of gas adsorption and separation. Porous liquids introduced fluid properties into the porous solid, combining the advantages of both porous solids and liquids. , Porous solids such as porous organic cages (POCs), metal–organic frameworks (MOFs), or zeolitic imidazolate frameworks (ZIFs) provide permanent porosity with rich gas adsorption behaviors. Meanwhile, liquids have a great ability to dissipate heat during adsorption and regeneration processes. , Also, liquids do not suffer from mechanical fatigue or physical aging, which is common in solid materials. , As of today, four types of porous liquids have been applied to gas adsorption or separation. ,, Type I PL is a neat liquid composed of one type of molecule that provides permanent intrinsic porosity. Type II PL combines the porous host and solvent, such as the porous organic cages solvated in the sterically hindered crown-ether liquids. Type III PL shares the same combination method as that of type II PL, while the solutes in type III PL usually are nanoparticles instead of organic cages. , Type IV PL is another single-component liquid with a lower melting point at room temperature . Among them, type II and type III PLs attract much attention due to the large combination of the porous host and solvent, which provides potential tunable applications for gas capture. , …”
Section: Introductionmentioning
confidence: 99%
“…These new SFNs have significant liquid flow behavior at room temperature without any solvents, as a result of the organic oligomers functioning as fluidic media to ensure mobility. During the past decade, various studies have shown that SFNs bring better dispersion of core particles due to their fluidity and the potential resistance effect of organic oligomer chains, also providing better support for their applications in different fields, such as tribology, flame retardant, sensor, energy storage, , gas capture, etc.…”
Section: Introductionmentioning
confidence: 99%